2012
DOI: 10.1161/circulationaha.111.054361
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Factors and the Risk of Adverse Outcomes in Women With Suspected Preeclampsia

Abstract: Background An imbalance in circulating angiogenic factors plays a central role in the pathogenesis of preeclampsia. Methods and Results We prospectively studied 616 women who were evaluated for suspected preeclampsia. We measured plasma levels of antiangiogenic soluble fms-like tyrosine kinase 1 (sFlt1) and proangiogenic placental growth factor (PlGF) at presentation, and examined for an association between sFlt1/PlGF ratio and subsequent adverse maternal and perinatal outcomes within 2 weeks. The median [25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
412
2
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 558 publications
(463 citation statements)
references
References 32 publications
17
412
2
9
Order By: Relevance
“…7 Apart from being a test to diagnose preeclampsia, recent research has shown that the sFlt-1/PlGF ratio is also strongly associated with subsequent maternal and perinatal adverse outcomes. 8 In women presenting at <34 weeks of gestation, the sFlt-1/PlGF ratio performs better than other currently available clinical signs and laboratory tests, like BP, and serum concentrations of creatinine, uric acid, and ALT in the prediction of adverse outcomes. 8 Furthermore, the sFlt-1/PlGF has been found to discriminate well between patients with preexisting hypertension or gestational hypertension and patients with superimposed preeclampsia.…”
Section: Sflt-1/plgf Ratio As a Diagnostic Testmentioning
confidence: 96%
See 1 more Smart Citation
“…7 Apart from being a test to diagnose preeclampsia, recent research has shown that the sFlt-1/PlGF ratio is also strongly associated with subsequent maternal and perinatal adverse outcomes. 8 In women presenting at <34 weeks of gestation, the sFlt-1/PlGF ratio performs better than other currently available clinical signs and laboratory tests, like BP, and serum concentrations of creatinine, uric acid, and ALT in the prediction of adverse outcomes. 8 Furthermore, the sFlt-1/PlGF has been found to discriminate well between patients with preexisting hypertension or gestational hypertension and patients with superimposed preeclampsia.…”
Section: Sflt-1/plgf Ratio As a Diagnostic Testmentioning
confidence: 96%
“…4,5 Compared with normal pregnancies, the serum concentration of the antiangiogenic soluble Fms-like tyrosine kinase 1 (sFlt-1) is markedly increased, whereas that of placental growth factor (PlGF) is decreased in preeclampsia. 4,[6][7][8][9][10] Because of the reciprocal changes of these markers, the ratio of sFlt-1/PlGF appears to be a superior marker of (early onset) preeclampsia compared with the individual values of these markers. 7,11 In the 3 complicated pregnancies of this grand round, we used the sFlt-1/PlGF ratio as a biomarker to differentiate among superimposed preeclampsia, activation of the underlying disease, or the combined occurrence of these 2 conditions.…”
mentioning
confidence: 99%
“…We found that the plasma sFlt1/PlGF ratio on presentation predicts adverse maternal and perinatal outcomes (occurring within two weeks) in the preterm setting. This simple, quantitative, rapid test outperformed the standard battery of clinical diagnostic measures including blood pressure, proteinuria, uric acid, and other laboratory assays 57 . Importantly, sFlt1 and/or PlGF levels at presentation were strongly associated with the remaining duration of pregnancy 53,[57][58][59][60] .…”
Section: Clinical Implications For Diagnosis and Treatment Of Preeclamentioning
confidence: 98%
“…This simple, quantitative, rapid test outperformed the standard battery of clinical diagnostic measures including blood pressure, proteinuria, uric acid, and other laboratory assays 57 . Importantly, sFlt1 and/or PlGF levels at presentation were strongly associated with the remaining duration of pregnancy 53,[57][58][59][60] . We also recently evaluated the role of sEng measurements and found that it has comparable performance to sFlt1/PlGF ratio 61 .…”
Section: Clinical Implications For Diagnosis and Treatment Of Preeclamentioning
confidence: 98%
“…The sFlt/PlGF ratio distinguishes preeclampsia (or SIPE) from either GH or CHTN, especially before 34 weeks of GA (29). Very high ratios before 34 weeks of GA in women with suspected preeclampsia predict the occurrence of adverse maternal or perinatal outcomes within a 2-week horizon and are associated with imminent delivery, whether for maternal or fetal indications (29,30). In this sense, one might imagine that such risk stratification could aid in more efficient clinical resource allocation among hypertensive gravidas, although it seems unlikely in the absence of compelling, well designed, and adequately powered prospective trials, that discrimination would be adequate to allow some women to be discharged, whereas others remain in hospital, based on these tests alone.…”
Section: Roles In Diagnosis and Preeclampsia Predictionmentioning
confidence: 99%